DEVELOPMENT OF A SCOUT MOVEMENT-BASED MENTAL HEALTH LITERACY MODULE TO PREVENT BULLYING - Selestina Vilmas Ngoranubun; Ahmad Guntur Alfianto; Rahmaniah Rahmadhani; Mizam Ari Kurniyanti (KHD Production, 2024)
Bullying is a negative behaviour that has an impact on mental health problems. Cases at school mean that bullying is often carried out by students/teenagers. Scout is one of the movements in schools, an agent of change, and an example of the values of school leaders. The literacy module can be a health promotion medium to prevent bullying. This research aims to develop a mental health literacy module based on the Scout movement to prevent bullying. This research is development research by testing modules. Design with a 4D model approach (definition, design, development, and dissemination). The respondents in this study were experts in mental and community nursing, as well as four scout teachers. The assessment uses the content validity ratio (CVR) and Content Validity Index (CVI). The results were at the definition stage that there was a bullying problem in schools, at the design stage with the creation of a literacy module based on the scout movement, at stage three development with the results of CVR (20.5) and CVI (0.46) and stage three dissemination of the module. Four experts carried out a series of 4 stages of analysis of module development with the development results with a ratio of 3 statements that needed to be accepted on the feasibility and accuracy indicators. However, from the overall results, the validity of the content is stated to be appropriate. The conclusion that the development of a mental health literacy module based on the Scout movement to prevent bullying was declared appropriate by four experts.